Science, Politics and the Public Good - Rupke, Nicolaas A. author. aut Link
XV, 260 p.
Keywords: An exploration of the relationship between scientific ideas, technology, government and politics, demonstrated by examples from the last 150 years, including the birth of the NHS, the Channel Tunnel, radiation protection, the atomic bomb and power, and nuclear power in the US and USSR.